Pengembangan website Monitoring Stok Barang Supplier dengan Sistem Rekomendasi menggunakan metode Collaborative Filtering pada Ud. Pekanbaru Jaya - Oddy Virgantara Putra; Dihin Muriyatmoko; Harris Abdillah Faqih (Ikatan Ahli Informatika Indonesia, 2024)
Pekanbaru Jaya, a goods distribution store, frequently faces challenges in monitoring supplier stock and ordering goods, leading to stockouts and operational inefficiencies. This study aims to design and implement an effective and efficient stock monitoring system using the Collaborative Filtering method. This method is chosen for its ability to predict items that users might like based on the opinions of other users, providing accurate recommendations even with limited content information. The system will also employ the Waterfall model in its development, ensuring that each development phase is conducted in a structured and well-documented manner. The implementation of this system is expected to assist UD. Pekanbaru Jaya in managing assets and inventory, ensuring sufficient stock availability, reducing the risk of stockouts, and optimizing resource utilization. The results of this study demonstrate that the developed system can enhance efficiency in stock management and provide a better shopping experience for customers through the online store.